Smart cities of today and tomorrow. Better technology, infrastructure and security. - Pelton, Joseph N.; Singh, Indu B. (Springer, 2019)
The book presents the latest trends in city planning in light of new technologies and security. Scores of cities around the world have begun planning what are known as "smart cities." These new or revamped urban areas use the latest technology to make the lives of residents easier and more enjoyable. They will have automated infrastructures such as the Internet of Things, "the Cloud," automated industrial controls, electronic money, mobile and communication satellite systems, wireless texting and networking. With all of these benefits come new forms of danger, and so these cities will need many safeguards to prevent cyber criminals from wreaking havoc. The book explains the advantages of smart cities and how to design and operate one. Based on the practical experience of the authors in projects in the U.S. and overseas in Dubai, Malaysia, Brazil and India, it tells how such a city is planned and analyzes vital security concerns that must be addressed along the way. Most people eventually live in smart cities. What are the advantages and the latest design strategies for such ventures? What are the potential drawbacks? How will they change the lives of everyday citizens?
Keywords: Stadtplanung; Technologie; Infrastruktur; Öffentliche Sicherheit; Informationstechnologie; Verkehr; Technische Infrastruktur; Smart City; Stadtsystem; Digitalisierung; Vernetzung; Internet; Datennutzung; Cybersicherheit; Resilienz; Steuerung; Datensicherheit